2003
DOI: 10.1097/01.lab.0000059927.97515.fd
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal Growth Factor-Induced Epithelio-Mesenchymal Transition in Human Breast Carcinoma Cells

Abstract: SUMMARY: PMC42-LA cells display an epithelial phenotype: the cells congregate into pavement epithelial sheets in which E-cadherin and ␤-catenin are localized at cell-cell borders. They abundantly express cytokeratins, although 5% to 10% of the cells also express the mesenchymal marker vimentin. Stimulation of PMC42-LA cells with epidermal growth factor (EGF) leads to epithelio-mesenchymal transition-like changes including up-regulation of vimentin and down-regulation of E-cadherin. Vimentin expression is seen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
117
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(125 citation statements)
references
References 66 publications
7
117
0
1
Order By: Relevance
“…Expression of the cell-cell adhesion molecule Ecadherin correlates with epithelial differentiation and and loss of E-cadherin may induce invasive growth of cancer cells (Batlle et al, 2000;Ackland et al, 2003). Our results showed that all YD cell line expressed E-cadherin.…”
Section: Discussionsupporting
confidence: 54%
“…Expression of the cell-cell adhesion molecule Ecadherin correlates with epithelial differentiation and and loss of E-cadherin may induce invasive growth of cancer cells (Batlle et al, 2000;Ackland et al, 2003). Our results showed that all YD cell line expressed E-cadherin.…”
Section: Discussionsupporting
confidence: 54%
“…Presumably, such a reduction in the levels of adhesion molecules plays a major role in prostate cancer progression (Wells, 2000). How EGFR signalling limits cadherin-mediated adhesions is still being deciphered (Ackland et al, 2003;Cozzolino et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…These cytokeratins are present in the relatively well-differentiated breast cancer lines including MCF-7 line but absent in the mesenchymal MDA-MB-231 line. PMC42-LA is heterogeneous with respect to some markers including vimentin, which suggests some plasticity with respect to phenotype (Ackland et al, 2003a).…”
Section: Evidence Of Emt In Breast Cancermentioning
confidence: 99%
“…A significant feature of PMC42-LA cells is that exposure of cells to EGF induces an EMT (Ackland et al, 2003a), including downregulation of E-cadherin and increased motility. This is typical of other systems in which EMT has been induced, such as the rat bladder cancer cell line NBT-II and the mouse mammary ScP-2 cell lines, and is also consistent with the lack of E-cadherin seen in a range of human breast carcinoma cell lines that showed in vitro invasiveness Nieman et al, 1999), as discussed above.…”
Section: Evidence Of Emt In Breast Cancermentioning
confidence: 99%